MODIFIKASI PROSES PENGHALUSAN GULA AREN MENJADI GULA SEMUT MENGGUNAKAN MESIN GILING DI KELOMPOK TANI HUTAN BUNIKASIH - Suryatini, Fitria; Dwiartomo, Bolo; Mulia, Sandy Bhawana; Salam, Abyanuddin (PUAN INDONESIA, 2024)
Palm sugar is a food commodity with good economic value compared to the production of palm sugar in the form of bulk blocks, especially if it can meet export standards. One of the production centers for ant palm sugar is in Buni Kasih Village, Cupunegara Village, Cisalak District, Subang Regency, West Java. To produce palm sugar, several machines are needed in the process, including evaporation, crystallization, roasting, grinding and sifting. One of the problems that occur in the production process is milling. The existing machine always produces a process of melting palm sugar every five minutes, the process is carried out so that it must always be cleaned and takes quite a long time, thereby reducing the productivity of the machine which is quite significant. There are two possible causes for the melting, namely engine construction errors or engine speed that is too high around 2200 rpm. The engine modification process was carried out by replacing the gasoline engine drive with high rpm to an electric motor with a rotation of 1400 rpm along with modifications to the mount. Setting the reduction of engine speed is done by using a pulley-belt system. Tests were carried out on engine rotation between 500 rpm to 1000 rpm. Optimal rotation is obtained at 900 rpm where 90% of the powdered sugar produced by the mill is successfully sieved to be ready for packaging, while 10% is re-milled. At 1000 rpm the resulting powdered sugar can reach 95%, but the machine must be cleaned every hour so that the sugar does not start to melt.